Trachoma prevalence in rural areas of eastern Iran - J. Sharifi-Rad (New Microbes and New Infections, 2016)
We investigated the prevalence of trachoma in rural areas of eastern Iran. We collected swabs from 150 children in three areas. Results of PCR showed presence of chlamydia in four boys (5.97%) and nine girls (10.84%). We suggest that in assessing the elimination of trachoma, WHO must consider border areas between countries.